Managing Complexity in Adaptive Case Management - Huber, Sebastian; Hauptmann, Adrian; Lederer, Matthias; Kurz, Matthias (S-BPM ONE Running Solutions: 5th International Conference S-BPM ONE 2013 Proceedings, Deggendorf, Germany, 2013)
The success of knowledge work represents one of the most important assets for businesses to date, and managers across all industries are searching for new ways to increase the productivity in this domain. Since traditional approaches, such as Business Process Management do not provide the suitable context to support knowledge intensive workflows, the recent trend of Adaptive Case Management has set out to address this issue by providing a framework that supports the required flexibility and enables an agile and dynamic environment. However, fundamental knowledge about this approach is currently scattered across a series of collective volumes and web blogs that tend to focus on isolated aspects or domain-specific challenges and solution approaches. As the ongoing discussion still lacks comprehensive theoretical literature, principles are driven mostly by individual circumstances, and common ideas are not transparent. The goal of this research effort is to provide a structured, domain-independent overview about the common principles in ACM and derive a set of distinct challenges in order to contribute to the general understanding of this paradigm. This work therefore discusses and consolidates existing literature, and subsequently focuses on the role of complexity in knowledge work to provide a foundation for the resulting challenge definitions. To complement the theoretical discussion, the final section of this paper provides a series of selected solution approaches that effectively support knowledge-intensive workflows. © 2013 Springer-Verlag.
WiSo2-Import:2015-10-05:579
Keywords: Adaptive Case Management; Business Process Management; Complexity Challenges